Study of Herbal Agro-Tourism as an Environmental Conservation Effort in Seberaya Village, Karo District, Indonesia - Theodora Ginting Munthe; Zulkarnain Lubis; Yusniar Lubis (Universitas Labuhanbatu, 2024)
Seberaya Village has a high biodiversity potential in flora, especially in herbal plants. The aim of this research is to identify the potential of herbal agrotourism as an environmental conservation measure to achieve sustainable development in the region. Descriptive qualitative method with observation and interview data collection. Data analysis techniques using the Miles and Huberman model. The results showed that there is potential for agritourism such as physical conditions, socio-economic conditions of the community and herbal plant commodities that support in Seberaya village. Visitors can enjoy cool, clean and beautiful natural panoramas, conduct tourism recreation with edufarming activities, namely the introduction of herbal plants, cultivation practices and herbal medicine processing. Herbal agritourism can contribute to environmental conservation by promoting organic practices, sustainable agriculture and raising awareness of the importance of conserving natural resources and biodiversity. With the existence of agritourism in Seberaya Village, it can promote local products, combat depopulation, protect nature in these areas, reduce the use of chemicals, meet the demand for healthy food, improve wildlife habitat, support local communities and encourage ethical choices, in line with the circular economy for a greener future